Local Perception of the Socio-Economic and Environmental Impacts of Typha domingensis (Pers.) in the Sahelian agro-systems of Niger - Bourahima, Adamou Moumouni; Manssour, Abdou Maman; Aboubacar, Awaiss (European Scientific Journal, ESJ, 2026)
The uncontrolled proliferation of Typha domingensis in the wetlands of Niger poses a major challenge. It disrupts the habits of local communities by altering their way of life and causes damage to their environment. Therefore, this study was conducted to provide some answers regarding the real impact of this species on the life of communities and on the environment, on the one hand, and, on the other hand, to clearly determine the opportunities it offers. It covered two sites more than 1000 km apart along the country’s Sahelian agro-ecological zone and 392 vegetable and/or rice farmers out of a total of 1009 producers. The methodological approach adopted was based on individual surveys combined with village general assemblies and interviews with agents from state technical services. The results show that Typha domingensis was first observed in the 1970s in southeastern Niger (Zinder region), while in the west of the country, it only appeared in the 1980s. The majority of respondents (73.2%) attributed its appearance to natural causes, while others (26%) favored supernatural ones. The remaining 0.8% believed it was introduced by humans. All respondents agree that the presence of Typha domingensis has significant negative impacts on agricultural production, fishing, and livestock farming. In addition to these drawbacks, the results also show that Typha domingensis is used in "construction and housing development" (88.1%), "human and animal food" (78.81%), "crafts" (7.3%), and "health" (0.3%). Regarding control techniques used to contain and/or eradicate Typha domingensis from wetland ecosystems, weed cutting remains the primary method. Although utilizing Typha as a source of biomass or biomaterials for construction or crafts is not in itself a method of species control, it can nevertheless contribute to its management by reducing the cost of certain operations and generating additional income.